Heart Failure and Total Hip Arthroplasty: What Are the Perioperative Outcomes and Complications? - Curtis, Gannon; George, Jaiben; Newman, Jared M.; Klika, Alison K.; Barsoum, Wael K.; Higuera, Carlos A. (The Journal of Hip Surgery, 2017)
Heart failure (HF) has been reported to cause morbidity and mortality after surgery. As the prevalence of HF and hip osteoarthritis increase, physicians are likely to observe a rise in the number of HF patients requiring total hip arthroplasty (THA). We asked (1) what perioperative outcomes can be expected for patients with HF after THA, and (2) does HF contribute to an increased risk of short-term complications after THA? The National Surgical Quality Improvement Program database was accessed to find patients with osteoarthritis who underwent THA from 2008 to 2014. The HF cohort included 177 patients, while the control group consisted of 64,619 patients. Demographics, comorbidities, outcomes, and complications were collected. Multivariate regression analysis was performed. HF patients were found to have longer hospital stays (β = 0.87; p = 0.004) and were less likely to be discharged home (OR = 1.77, p = 0.001) following THA. It also increased the risk for any complication (OR = 1.54, p = 0.011), mortality (OR = 3.67, p = 0.042), readmission (OR = 1.68, p = 0.041), cardiac arrest (OR = 8.44, p = 0.006), myocardial infarction (OR = 3.75, p = 0.014), and deep surgical site infection (OR = 3.62, p = 0.035). HF patients had longer hospital stays and were discharged to a facility after THA. Overall, they had an increased risk of any complication, readmission, cardiac arrest, myocardial infarction, and deep surgical site infection. Moreover, the mortality risk after THA was significantly high. Cardiac optimization could play a key role in the prevention of these adverse outcomes. Patients should be counseled prior to surgery.
Keywords: total hip arthroplasty; heart failure; complications